2023
DOI: 10.1186/s12890-023-02345-3
|View full text |Cite
|
Sign up to set email alerts
|

Developing a mortality risk prediction model using data of 3663 hospitalized COVID-19 patients: a retrospective cohort study in an Egyptian University Hospital

Abstract: Purpose Since the declaration of COVID-19 as a pandemic, a wide between-country variation was observed regarding in-hospital mortality and its predictors. Given the scarcity of local research and the need to prioritize the provision of care, this study was conducted aiming to measure the incidence of in-hospital COVID-19 mortality and to develop a simple and clinically applicable model for its prediction. Methods COVID-19-confirmed patients admitte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 38 publications
0
1
0
Order By: Relevance
“…The present prediction model included predictors reflecting the patients' demographics and preexisting conditions, which are common components of other risk stratification models (20,21). In our study, the in-hospital death risk showed a significant age gradient, supporting age as a strong predictor of mortality in hospitalized patients with COVID-19 (22).…”
Section: Discussionmentioning
confidence: 55%
“…The present prediction model included predictors reflecting the patients' demographics and preexisting conditions, which are common components of other risk stratification models (20,21). In our study, the in-hospital death risk showed a significant age gradient, supporting age as a strong predictor of mortality in hospitalized patients with COVID-19 (22).…”
Section: Discussionmentioning
confidence: 55%
“…COVID-19 is the second pandemic in the twenty-first century, accounting for more than 100 million cases and more than two million fatalities [27]. On August 20th, 2022, the number of documented patients in Egypt was 515,198, with nearly 24,786 deaths [28]. Variation in the severity of COVID-19 can be partially explained by the genetic background of the host and other risk factors like age, gender, and underlying clinical conditions [2].…”
Section: Discussionmentioning
confidence: 99%